1995
DOI: 10.1021/ja00106a077
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Ethylene-Ozone and Cyclohexene-Ozone Charge-Transfer Complexes in Cryogenic Matrixes

Abstract: In 1971 Bailey and co-workers reported the first observation of a charge-transfer complex of ozone with an aromatic system.1 23At the time complexes were suggested as possible

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Two photoreaction processes produce highly reactive species O­( 1 D) with O 2 from O 3 by irradiations at λ < 310 and 411 nm. Although another process to produce O­( 3 P) and O 2 from O 3 by longer-wavelength irradiation is also familiar, it is not of much importance with reference to the atmosphere because the transition coefficient is either very low or is optically inhibited. However, some researchers reported that molecular complexes composed of O 3 and several molecules like olefin, ethylene, dimethylsulfide, and so on , have intense absorption bands in the visible-light region, in contrast to the O 3 monomer, and that visible-light-induced oxygen-atom transfer from O 3 to the counter molecule can occur in these complexes. For example, an O 3 –ICl complex yields OICl by visible-light irradiation between wavelengths 470 and 750 nm, and an O 3 -dimethylsulfide complex yields dimethylsulfoxide upon red-light irradiation (λ = 700–740 nm) . The enhanced visible-light absorption and photoreaction mechanism of O 3 -molecule complexes are interesting in molecular chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Two photoreaction processes produce highly reactive species O­( 1 D) with O 2 from O 3 by irradiations at λ < 310 and 411 nm. Although another process to produce O­( 3 P) and O 2 from O 3 by longer-wavelength irradiation is also familiar, it is not of much importance with reference to the atmosphere because the transition coefficient is either very low or is optically inhibited. However, some researchers reported that molecular complexes composed of O 3 and several molecules like olefin, ethylene, dimethylsulfide, and so on , have intense absorption bands in the visible-light region, in contrast to the O 3 monomer, and that visible-light-induced oxygen-atom transfer from O 3 to the counter molecule can occur in these complexes. For example, an O 3 –ICl complex yields OICl by visible-light irradiation between wavelengths 470 and 750 nm, and an O 3 -dimethylsulfide complex yields dimethylsulfoxide upon red-light irradiation (λ = 700–740 nm) . The enhanced visible-light absorption and photoreaction mechanism of O 3 -molecule complexes are interesting in molecular chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…There are other hypotheses for the reaction mechanism: electron transfer with the formation of an ion–radical complex in the reactions of electron-donor substituted alkenes and H atom abstraction from ethylene . There are no data confirming the one-electron transfer for the reaction C 2 H 4 + O 3 → products in the gas phase . Several reaction channels after POZ have been considered for the gas-phase reaction …”
Section: Introductionmentioning
confidence: 99%
“…The observation of CT bands has been reported for some organic molecule-ozone complexes [4][5][6][7]. Jonnalagadda et al measured the CT band for the C 2 H 4 -O 3 complex in the Xe matrix [6]. The spectrum shows a maximum at ca.…”
Section: Discussionmentioning
confidence: 79%
“…Regarding the C 2 H 4 -O 3 system, we could not observe photoproducts spectroscopically upon irradiation at 405 nm, and there might be a "gap" in the CT band around this wavelength, whereas no such depletion of photolysis was found for other olefins. The observation of CT bands has been reported for some organic molecule-ozone complexes [4][5][6][7]. Jonnalagadda et al measured the CT band for the C 2 H 4 -O 3 complex in the Xe matrix [6].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation